Efficiency- and lifetime-limiting effects of commercially available UVC LEDs: a review - Grigory Onushkin; Jan Ruschel; Francesco Piva; Matteo Buffolo; Jens Rass; Lynn Davis; Nicola Trivellin; Carlo De Santi; Willem van Driel; Matteo Meneghini (JPhys Photonics)
This review is aimed at providing an overview of the technologies of currently-available UVC LEDs, on the challenges that these devices have to face, and on the peculiar features that these modern solid-state emitters exhibit. In particular, this paper is aimed at serving as a bridge between device developers and system manufacturers, by increasing awareness of the differences, both in terms of reliability and operation, that AlGaN-based UVC LEDs show with respect to their visible InGaN/GaN-based counterparts. In this view, this work reports performance and lifetime figures of both commercially-available and research-grade LEDs, showing their limitations in terms of temperature- and current-dependency of the emission spectrum. Both catastrophic and gradual processes that lead to device degradation are discussed, with a particular focus on the kinetics that device properties exhibit during prolonged operation. Moreover, also package-related degradation processes are investigated, which stand-out due to the peculiar structures and materials required to sustain both high-energy UV photons and high localized self-heating, while maximizing the optical efficiency of the LEDs. Ultimately, the data reported within this paper should help the final user in predicting and mitigating degradation effects, while also serving as a reference to manufacturers for the improvement of next generation devices.